2013
DOI: 10.1021/la4007668
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Agarose-graft-poly[3-dimethyl (methacryloyloxyethyl) ammonium propanesulfonate] Zwitterionic Graft Copolymers via ATRP and Their Thermally-Induced Aggregation Behavior in Aqueous Media

Abstract: A novel polysaccharide-based zwitterionic copolymer, agarose-graft-poly[3-dimethyl (methacryloyloxyethyl) ammonium propanesulfonate] (agarose-g-PDMAPS) with UCST, depending both on hydrogen bonding and electrostatic interaction, was synthesized by ATRP, and its aggregation behavior in aqueous media was investigated in detail. Proton nuclear magnetic resonance spectroscopy, Fourier transform-infrared spectroscopy, and gel-permeation chromatography were performed to characterize the copolymer. Thermosensitive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…26,30 It has been reported that the hydroxyl groups at the C-6 positions of polysaccharides are apparently favorable for the substitution reactions. In this work, the bromoisobutyryl-functionalized Agr (Agr-Br) macroinitiator was prepared via the reaction of hydroxyl groups of Agr with 2bromoisobutyryl bromide (BiBB) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,30 It has been reported that the hydroxyl groups at the C-6 positions of polysaccharides are apparently favorable for the substitution reactions. In this work, the bromoisobutyryl-functionalized Agr (Agr-Br) macroinitiator was prepared via the reaction of hydroxyl groups of Agr with 2bromoisobutyryl bromide (BiBB) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…22 Due to its biocompatibility, non-fouling and non-immunogenic attributes, 23 Agr has been widely explored for applications in the biomedical eld. 23,24,26,27 Thus, integration of Agr and QAS could lead to the formation of an antibacterial agent, which is soluble in aqueous media at low concentration and solidies as a hydrogel at high concentration. Agr is soluble/dispersible in aqueous media at a lower concentration.…”
Section: Introductionmentioning
confidence: 99%
“…RDRP techniques offer direct access to polymers bearing zwitterionic groups with previously unthinkable features, such as predefined molar masses and narrow molar mass distributions [163,[182][183][184][185][186][187][188][189] as well as well-defined functional end groups [61,166,182,[190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208]. Moreover, complex architectures, such as block copolymers [14,[46][47][48]166,167,169,173,187,, graft copolymers [164,213,237,[241][242][243][244]…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%
“…As observed under TEM, the amphiphilic copolymers still formed spherical micelles at same concentration (Figure S5b, Supporting Information). It was believed that the introduction of hydrophilic PEG segment into the block copolymer may weaken the interactions between P(AAm‐ co ‐AN) segments, resulting in decreased UCST …”
Section: Resultsmentioning
confidence: 99%
“…It was believed that the introduction of hydrophilic PEG segment into the block copolymer may weaken the interactions between P(AAm-co -AN) segments, resulting in decreased UCST. [ 20,31 ] The effect of polymer concentration on the UCST of the P5 was studied at micelle concentration of 0. (Figure 2 c).…”
Section: Ucst Phase Transition Of Copolymer In Pure Watermentioning
confidence: 99%